PUBLIC SERVICES AT THE TOMONI VILLAGE OFFICE, TOMONI DISTRICT, EAST LUWU REGENCY - Yuliana Ripa Tangdiong; Besse Herlina (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This research or study aims to analyze and explain about the implementation of public services at the Subdistrict of Tomoni (a village government office), Tomoni District, East Luwu Regency, about determinant of factor influencing (supporting and inhibiting) it, and about strategies needed to improve the quality of public services. A qualitative descriptive as type or kind of research. Amount 50 people of local community established as sample (by purposive sampling technique). All of data collected by use library research, observation, questionnaires, interviews, documentation technique. A Qualitative used to data analysis. Result, the implementation of public services which includes amount administrative services for letters of introduction and permits as required by community members at the Tomoni Village Office has not been optimal/effective. Internal factors that support public services are competence, coordination-internal cooperation, awareness and commitment, ethics of decency and integrity, motivation, leadership, and environment work. Meanwhile, the internal inhibiting factors are bureaucratic culture, infrastructure and facilities - technology, discipline, responsive/ empathetic attitude, and public service mechanisms. Supporting external factors are policies and community behavior. While the external inhibiting factors are socialization, supervision, management information systems (MIS), Environment and culture, and Coordination and external cooperation. The strategy to improve the quality of public services needed is to increase and develop all supporting and inhibiting factors.